Comparative genomic analysis of the Fructobacillus genus reveals important differences in amino acid metabolism - Mohamed, María Florencia (2021)
The Fructobacillus genus is a group of obligatory fructophilic lactic acid bacteria, recently reclassified from Leuconostoc due to phylogenetic and biochemical differences. These bacteria require the use of fructose or another electron acceptor for its growth, because of the lack of an alcohol-acetaldehyde dehydrogenase gene (adhE). Previously, some genomic differences were reported in Fructobacillus respect to Leuconostoc, suggesting a reductive evolution in carbohydrate metabolism caused by an adaptation to fructose-rich niches. In this work, we performed a comparative genomic analysis in the genus Fructobacillus to evaluate possible genomic and metabolic differences among species. For this, nine Fructobacillus genomes were used. As expected, the GC content was highly similar among this genus (43,9 ? 44,8 %mol); however, some differences were found in genome size and number of CDS being the genomes of F. durionis DSM 19113 and F. sp. CRL 2054 smaller (1,32 Mb) than F. tropaeoli genomes (1,66 ? 1,68 Mb). Six intact prophage regions (20,6 ? 30,5 kb) were identified in four strains whereas Type II CRISPR-Cas systems were found in five genomes. A bacteriocin-coding gene was only found in F. durionis DSM 19113. Plasmids and antibiotic resistance genes were not detected in the studied genomes. Phylogenetic analyses were done based on 16S rRNA sequences and Fructobacillus core-genome. Both phylogenetic trees allowed us to distinguish two different phylogroups in this genus. Phylogroup 1 was composed by F. sp. CRL 2054, F. durionis and F. fructosus strains, whereas F. ficulneus, F. pseudoficulneus, F. sp. EFB-N1 and F. tropaeoli strains formed part of phylogroup 2. A pangenome analysis showed important differences in presence/absence of genes between both groups. Consequently, annotation of genomes in COG and KEGG databases was performed to classify genes according to its metabolic function. The number of genes involved in COG categories E, F, H and P related with metabolism were significantly lower (p<0,05) in phylogroup 1. This group of strains also presented an important decrease in the number of genes involved in synthesis of five amino acids, when comparing to phylogroup 2 and L. mesenteroides ATCC 8293. This reduction in the amino acid metabolism was also observed experimentally in F. sp. CRL 2054 and F. tropaeoli CRL 2034. Finally, the presence of genes involved in central carbohydrate metabolism was evaluated among the strains. Differences were detected in genes related to fructose metabolism (fk, gpi) and genes related to the use of electron acceptors (D- and L- ldh, adh, budC, yjlD); however, those variations were not always related to the phylogeny between organisms. In conclusion, two groups with important genomic differences were identified in Fructobacillus; moreover, the presence of genes involved in NADH reoxidation and fructose intake was variable throughout the genus.